A 'real-world' analysis of risk factors for post liver transplant delirium and the effect on length of stay. Issue 10 (October 2020) - Tavabie, Oliver D.; Colwill, Michael; Adamson, Robbie; McPhail, Mark J.W.; Bernal, William; Jassem, Wayel; Prachialias, Andreas; Heneghan, Michael; Aluvihare, Varuna R.; Agarwal, Kosh
Abstract : Background: The development of delirium has been previously demonstrated to be associated with an increased risk of mortality and length of stay post liver transplant (LTx) with multiple risk factors being identified in previous studies. In this study, we have aimed to identify the most important variables associated with the onset of post-LTx delirium and understand the effect on length of stay (LOS). Methods: All liver transplants for chronic liver disease between 1 August 2012 and 1 August 2017 were included ( n = 793). Data were collected for analysis retrospectively from electronic patient records. Results: Delirium is associated with an overall increased hospital and ICU LOS but not one-year mortality. The risk of developing post-LTx delirium was the greatest among patients: with post-LTx sepsis, who required renal sparing immunosuppression, who received donation after cardiac death (DCD) grafts and who were older. Patients with autoimmune hepatitis, primary biliary cholangitis or primary sclerosing cholangitis seemed to be at lower risk of post-LTx delirium. However, global patient LOS was only prolonged in patients with sepsis and renal failure. Conclusion: Many of the risk factors previously described to be associated with the development of post-LTx delirium were not demonstrated to be significant in this study. Sepsis, renal failure, older age and DCD use are associated with delirium post-LTx. It is unclear if this syndrome is an independent risk factor for increased LOS or if it is a symptom of well established syndromes associated with increased LOS. The role for prophylactic strategies to reduce the incidence of post-LTx delirium is therefore unclear.